Enhanced cooperation and integration between Indonesia and Timor Leste scoping study. (Metro Manila, Philippines Asian Development Bank, 2019)
This report recommends how Indonesia and Timor Leste can enhance cross border cooperation and integration to help boost economic growth and reduce poverty. It focuses on opportunities in the tourism and livestock sectors and reviews transport connectivity, trade, and the business and investment climate. The report was undertaken at the request of the governments of Indonesia and Timor-Leste and involved extensive consultations with government, the private sector, and civil society.
Keywords: Indonesia -- Economic integration; Electronic books